Some new inequalities of Hermite-Hadamard type for s-convex functions with applications - Khan, Muhammad Adil; Chu, Yuming; Khan, Tahir Ullah; Khan, Jamroz (Open mathematics (Warsaw, Poland), 2017)
In this paper, we present several new and generalized Hermite-Hadamard type inequalities for s-convex as well as s-concave functions via classical and Riemann-Liouville fractional integrals. As applications, we provide new error estimations for the trapezoidal formula.